Fixed Asset Management at the Lebak Regency Transportation Service - Mayang Mulyasari (International Journal of Social Sciences Review, 2023)
This research focus is about how the process of assets management is still running in the Department of Transportation of Lebak Regency. Has the management process gone well according to the mechanism or has appropriate based on the rule that has been established. The problem in this research for all this time is the rule of inventoried management of goods held based on the rule that has been determined by Lebak Regency Number 7-year 2018, and also the rule of domestic affair minister Number 47-year 2021. This research is to gain information of how the assets management in the Department of Ttransportation of Lebak Regency is running. This research is descriptive qualitative research. This primer data collection technique comes with observation, interview and documentation, while the secondary data collection technique and the source of other secondary data source of data. Theresearcher uses the theory assets management model of Doli D. Siregar with the asset’s indicator of: assets inventoried; legal audit; assets value, assets optimized; surveillance and control. In choosing the informant, the researcher uses purposive techniques. The result of the research shows that the assets management is still in the Department of Transportation of Lebak Regency and is not still running well yet. Due to lots of problem that exist in the stage of assets management process as an example is the renewal of labeling/ coding of physical assets that haven't been changed yet, the missing and the broken legal of vehicle assets, infrastructure of assets secure which is still lack, and the uniaxiality of optimized implementation of terminal assets.